Alcohol Attributable Fraction for Injury Morbidity from the Dose‐Response Relationship of Acute Alcohol Consumption: Emergency Department Data from 18 Countries. (27th July 2015) - Cherpitel, Cheryl J.; Ye, Yu; Bond, Jason; Borges, Guilherme; Monteiro, Maristela; Chou, Patricia; Hao, Wei
Abstract: Aims: To calculate the alcohol‐attributable fraction (AAF) of injury morbidity by volume of consumption prior to injury based on newly reported relative risk (RR) estimates. Design: AAF estimates based on the dose‐response RR estimates obtained from previous pair‐matched case‐crossover fractional polynomial analysis of mean volume in volume categories were calculated from the prevalence of drinking prior to injury in each volume category. Setting: Thirty‐seven emergency departments (EDs) across 18 countries. Participants: Probability samples of patients, with equal representation of each shift for each day of the week, totaling 14, 026 who arrived at the ED within six hours of injury from ED studies conducted between 2001 and 2011. Measurements: AAF was analyzed by gender, age (18‐30; >30), cause of injury (traffic, assault, fall, other), and country detrimental drinking pattern (DDP). Findings: For the EDs analyzed, 16.4% of all injuries were estimated to be attributable to alcohol, and the AAF did not vary by age but was over twice as large for males (20.6%; 19.3‐21.8) than for females (8.6%; 7.5‐9.7%). While females were at greater risk of injury than males at higher volume levels, lower prevalence of women drinking at higher levels contributed to overall lower AAF for women. Assault‐related injuries showed the largest AAF (44.1%; 37.6‐42.6). AAF was slightly higher for injuries from falls (14.3%; 12.9‐15.7) than motor vehicle crashes (11.1%; 9.3‐12.9). AAF was higher in those countries with a DDP of 3 (18.6; 17.5‐19.7) and 4 (19.4%; 17.3‐21.6) than those with a DDP of 2 (12.0%; 10.5‐13.5). Conclusions: Alcohol‐attributable injuries presenting in emergency departments are higher for males than females, for violence‐related injuries compared with other types of injury, and for countries with more detrimental drinking patterns compared with those with less detrimental patterns.